THE ROLE OF MICROFINANCE INSTITUTIONS IN ADDRESSING FINANCIAL BARRIERS AND SUPPORTING SMES GROWTH IN RURAL NYARUGENGE DISTRICT, RWANDA - Ituze, Nicolas (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Small and medium-sized enterprises (SMEs) are essential for innovation, job creation, and poverty reduction in developing economies, yet many in Rwanda continue to face financing challenges that limit their growth. In Nyarugenge District, where SMEs drive local commerce, high financial barriers, limited credit access, and inadequate financial literacy hinder their sustainability. This study examines how financial constraints, financial literacy, and access to microfinance services influence SME growth. A quantitative approach was applied using structured questionnaires distributed to 180 purposively selected SMEs. The instrument, adapted from validated studies and contextualized for Rwanda, measured access to microfinance, financial barriers, financial literacy, and SME growth. Data were analyzed using SEM in SmartPLS 4, including reliability and validity assessments, and hypothesis testing. Findings show that access to microfinance services significantly enhances SME growth, while financial barriers negatively affect it. Financial literacy had the strongest positive influence, underscoring its importance in effective financial management and entrepreneurial success. The study concludes that improving SME financial literacy and reducing financing barriers are essential for sustainable growth, and recommends that policymakers and microfinance institutions design integrated programs that expand credit access and strengthen managerial capacity to boost SME competitiveness in Rwanda.